A semi-solid forming process of silicon-aluminum alloy
Through the semi-solid forming process of silicon-aluminum alloy, powder spraying technology and heat treatment, the problem of insufficient mechanical properties of aluminum alloy is solved, significantly improving its strength, plasticity and corrosion resistance, and extending its service life.
Patent Information
- Application Number
- CN202411394645.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing aluminum alloys have poor mechanical properties in semi-solid forming processes and are difficult to meet actual needs.
采用硅铝合金的半固态成形工艺,通过合金粉末与铝液的喷粉技术在惰性气体搅拌下形成半固态浆料,结合热处理和表面处理,提高合金的力学性能和耐腐蚀性能。
It significantly improves the strength, plasticity and wear resistance of silicon-aluminum alloys, extends its service life, and enhances corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy casting, in particular to a semi-solid forming process of a silicon-aluminum alloy. Background Art
[0002] Aluminum alloy has the characteristics of low density, high specific strength, and easy processing and forming. As a lightweight metal material, it is widely used in the manufacturing of equipment and parts such as aerospace, automobiles, and ships. Semi-solid forming is a process for processing and casting aluminum alloys. During the solidification process of the liquid metal, it is vigorously stirred to break the dendrite network skeleton formed in the casting and disperse it into a granular structure to form a semi-solid metal liquid, which is then die-cast into the required blank. This requires the aluminum alloy to have good casting fluidity and mechanical processing properties, but the aluminum alloys commonly used for semi-solid forming have poor mechanical properties and are difficult to meet actual needs. Therefore, we propose a semi-solid forming process for silicon aluminum alloy. Summary of the invention
[0003] The object of the present invention is to provide a semi-solid forming process of silicon aluminum alloy to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a semi-solid forming process of silicon aluminum alloy, comprising the following processes:
[0005] The raw materials are mixed, heated and melted to form aluminum liquid; alloy powder is added and semi-solid slurry is made to obtain semi-solid slurry; die casting is performed, and heat treatment is performed to obtain silicon aluminum alloy.
[0006] Furthermore, the aluminum liquid includes the following components: by mass, silicon Si: 7.0-9.5%, magnesium Mg: 0.30-0.60%, copper Cu: 0.18-0.25%, titanium Ti: 0.05-0.20%, manganese Mn: 0.04-0.08%, iron Fe: ≤0.12%, zinc Zn: ≤0.05%, zirconium Zr: 0.04-0.06%, rare earth element RE: 0.20-0.60%, and the balance is aluminum Al;
[0007] The rare earth element RE is a mixture of one or more of yttrium Y, cerium Ce, and lanthanum La.
[0008] Furthermore, the heating melting temperature is 730-780°C.
[0009] In the above technical solution, compared with metallic aluminum, silicon has a higher relative density and linear expansion coefficient. As a face-centered cubic crystal, adding it to aluminum alloy can effectively improve the flow properties of the alloy, reduce the shrinkage of the alloy, and reduce defects such as looseness; and as the silicon content increases, the hardness and strength of the silicon-aluminum alloy increase. However, the hypereutectic silicon-aluminum alloy produced by excessive silicon has a large amount of blocky primary silicon in its structure, which will reduce the performance of the alloy.
[0010] Copper has a low solubility in aluminum and can form a limited solid solution, which causes lattice distortion in the solid solution and hinders dislocation movement, thereby producing solid solution strengthening. It can also form intermetallic compounds with silicon, manganese, aluminum and other elements in the system, further improving the mechanical properties and heat resistance of silicon-aluminum alloys. However, too much copper will affect the plasticity and corrosion resistance of the alloy, increase the alloy's tendency to hot cracking, and deteriorate its casting properties.
[0011] Magnesium has a high solubility in aluminum and a higher solid solution strengthening rate, which can effectively improve the strength of the alloy; it can form a strengthening phase Mg2Si with silicon in the dark, further improving the tensile strength and yield strength of the alloy. However, too much magnesium will cause oxidation and inhalation of the alloy; too little magnesium will not have a significant strengthening effect on the alloy.
[0012] Manganese can improve the toughness of the alloy to a certain extent, reduce the electrode potential difference in aluminum, and improve its corrosion resistance; it can form dispersed particles MnAl6 with aluminum to prevent its recrystallization and coarsening. Iron is prone to form coarse needle-shaped brittle phases in silicon-aluminum alloys, deteriorating the mechanical properties and corrosion resistance of the alloy; while manganese can form intermetallic compounds with it, transforming the brittle phase from needle-shaped to block-shaped, reducing its harm.
[0013] Titanium forms Al3Ti in aluminum alloy, which acts as a heterogeneous nucleation core in the α-Al solid solution and refines the α-Al dendrites. Zirconium can form intermetallic compounds with aluminum and act as a heterogeneous nucleation core to refine the grains.
[0014] As a modifier, rare earth elements can refine the eutectic silicon structure; they promote each other with the above-mentioned grain refiners and have a better refinement effect on α-Al; they can also form intermetallic compounds, strengthen grain boundaries, and reduce the thermal cracking tendency of the alloy; they can degas and purify the melt and improve the mechanical properties of the alloy.
[0015] Furthermore, the semi-solid slurrying adopts one or more of mechanical stirring method, mechanical vibration method, electromagnetic stirring method, ultrasonic vibration method, pulsed magnetic field method, gas stirring method, solid-liquid mixing method, near liquidus casting method, strain induced melting activation method, serpentine channel casting process, cooling ramp method, internal cooling method, damping cooling tube method, and dispersed mixing rheology method.
[0016] Furthermore, the process of semi-solid slurrying is as follows: cooling the aluminum liquid to a slurrying temperature of 690-710°C, inserting a powder spraying rod, and spraying alloy powder into the aluminum liquid using an inert gas as a working gas;
[0017] The particle size of the alloy powder is 0.5-3.0 mm, the rotation speed of the powder spraying rod is 800-1000 rpm, and the alloy powder is 6-12% of the mass of the aluminum liquid;
[0018] The inert gas is argon or nitrogen.
[0019] In the above technical solution, the inert gas introduced in the semi-solid slurrying process has a strong stirring effect on the aluminum liquid, so that a large number of non-dendritic structures can be generated inside it; and the blown inert gas has a certain melt refining effect, which can purify the melt, thereby obtaining a more ideal semi-solid slurry. Under the strong stirring effect of the inert gas, α-Al and eutectic silicon are finer, the slurry structure is refined, and the mechanical properties of the obtained silicon aluminum alloy are improved. The powder spraying rod can also be used as a cooling medium to absorb heat, which helps to obtain a semi-solid slurry.
[0020] While the air flow is stirring, alloy powder is added, and the temperature difference between the alloy powder and the aluminum liquid is used to make the melt obtain a certain degree of supercooling, which provides a phase change driving force for nucleation and reduces the critical nucleation radius; the alloy powder melts in the aluminum liquid, providing a large number of foreign eutectic silicon particles and fine primary silicon, which promotes the non-spontaneous nucleation of the initial silicon in the melt. The strong convection generated by the air flow stirring causes temperature gradients and concentration gradients in some micro-regions inside the aluminum liquid, which can promote nucleation and inhibit grain growth; the role of nucleation hard points in the alloy powder further increases the number of nucleation points in the melt, improves the nucleation rate of the aluminum liquid, and thus makes the semi-solid slurry have a good structure.
[0021] The slurrying temperature is selected to be about 10°C above the solid-liquid temperature of the aluminum liquid, so that the melt can be quickly supercooled to the solid-liquid range, and a large number of fine nuclei are formed under the conditions of external particles and uniform temperature field. A large number of nucleation particles restrain each other and grow, and finally form relatively fine primary silicon. If the slurrying temperature is too low, the primary phase has begun to nucleate and crystallize, and the injection of alloy powder produces a certain degree of supercooling, which will cause the primary phase that has been nucleated to grow rapidly, and the injected powder cannot play an effective role as a nucleation particle. If the slurrying temperature is too high, the alloy powder will melt in large quantities after injection, and it will not play a supercooling nucleation role.
[0022] If too little alloy powder is added, the aluminum liquid will be cooled to a small extent, resulting in a small degree of supercooling, and some eutectic phases and primary phase nuclei in the aluminum liquid will remelt. If too much alloy powder is added, the injection time of the alloy powder will be prolonged, the initial phase will begin to grow, and the aluminum liquid will be in a semi-solid state. The alloy powder injected later cannot be dispersed, and eventually aggregates and grows, and the initial phase begins to coarsen.
[0023] Furthermore, the alloy powder includes the following components: by mass, silicon Si: 20-25%, titanium Ti: 8.2-19.9%, boron B: 3.8-9.1%, and the balance is aluminum Al.
[0024] Furthermore, in the alloy powder, Ti=(2.15-2.20)×B in mass percentage.
[0025] Furthermore, the alloy powder is mixed with aluminum powder, titanium powder and boron powder, cold pressed, hot pressed and sintered to generate an aluminum / titanium boride composite; and mixed with an aluminum silicon alloy, melted and sprayed to obtain the composite.
[0026] Furthermore, the process conditions of cold pressing are: pressure 3-5T, holding time 60-90s;
[0027] The process conditions of hot pressing sintering are: sintering temperature 1600-2000°C, pressure 25-30MPa, heat preservation 60min, protective atmosphere is argon;
[0028] The process conditions of spray deposition are as follows: the working gas is nitrogen, the diameter of the flow tube is 3.5 mm, the melt temperature is 680-740°C, the atomization deposition distance is 400-470 mm, and the atomization gas pressure is 0.8-1.5 MPa.
[0029] In the above technical solution, the alloy powder is obtained by spray deposition, and the alloy melt crystallizes and nucleates under quenching. The primary α-Al does not have time to grow, and the eutectic point moves to the right, so that the grain size is refined. As the particle size of the alloy powder decreases, the average grain size of the primary aluminum and eutectic phase in its structure becomes finer, and more nucleation points can be obtained by spraying into the aluminum liquid with the same mass. The alloy powder has a high silicon-aluminum ratio, and the fine initial silicon has more nucleation points, which helps to obtain a better microstructure.
[0030] In the early stage of alloy powder preparation process, in the aluminum-titanium-boron system, under the influence of thermodynamics of hot pressing sintering, titanium boride (TiB2) reacts in situ in the aluminum melt medium and deposits to form nearly spherical particles; it has good wettability with aluminum metal, so that it can be evenly distributed in the aluminum-silicon alloy, which is conducive to spray deposition and preparation of alloy powder; and aluminum also helps the refinement of TiB2. When it is added to the aluminum liquid, it can increase the dislocation density of the silicon-aluminum alloy produced, and the chances of dislocations intersecting with each other during the slip process during deformation increase, and the resistance increases; TiB2 is a stable refractory compound with the characteristics of high melting point, high hardness, and high elastic modulus. It can act as a hard particle reinforcement and bear a certain load; and it can act as a heterogeneous nucleation core, play a solid solution strengthening role, refine the organization, promote the transformation of the eutectic organization to a network configuration, hinder the aggregation of the brittle eutectic phase, so that the strength and plasticity of the silicon-aluminum alloy material produced are improved, and the corrosion resistance and friction and wear ability are improved. TiB2 is added to the aluminum liquid in the form of alloy powder during the slurry making process. It has good dispersibility and can effectively avoid its rapid sedimentation in the melt and alleviate the refinement decay phenomenon. It inhibits the segregation of silicon at the interface and serves as an effective nucleation core for primary α-Al, thereby improving the nucleation efficiency and refining the grains.
[0031] Furthermore, the process conditions of die casting are: die casting temperature 300-350°C, injection speed 1.5-2.5 m / s, injection pressure ratio 30-50 MPa, boost pressure 60-80 MPa, and holding time 8-12 s.
[0032] Further, the heat treatment process includes solution heat treatment and artificial aging;
[0033] The process conditions of solution heat treatment are: temperature 500-550℃, duration 4-8h; cooling in 40-60℃ water, duration <10s; taking out, natural aging for 24h;
[0034] The process conditions of artificial aging are: temperature 160-200℃, time 4-8h.
[0035] In the above technical scheme, the alloy is kept at the solution temperature so that the strengthening phase in the alloy is fully dissolved into the alloy matrix, the supersaturation of the alloy matrix is increased, and a supersaturated solid solution is formed; and the organization is homogenized, and the spheroidized silicon phase provides a driving force for the precipitation phase during aging treatment. The strengthening phase (intermetallic compound) is dissolved during the solution heat treatment, and a supersaturated solid solution is formed after quenching. It is dispersed and precipitated during the aging treatment, and the size is small, which plays a precipitation strengthening role.
[0036] Furthermore, the silicon aluminum alloy is surface treated, and the specific process is as follows:
[0037] Plasma spraying technology is used to spray alloy powder onto the surface of silicon-aluminum alloy to form a hardened layer;
[0038] Hydrothermal treatment forms a corrosion-resistant layer; sealing treatment forms a closed layer.
[0039] Furthermore, the process conditions of plasma spraying are: argon flow rate 80-90 L / min, hydrogen content 22-26%, spraying power 46-50 kW, and spraying distance 120-135 mm.
[0040] In the above technical solution, the alloy powder is heated to a molten state through plasma spraying technology, and then sprayed on the surface of the silicon-aluminum alloy to form a high-silicon-aluminum coating (referred to as a hardened layer) with high doping of titanium boride, which has good bonding performance with the silicon-aluminum alloy; compared with the silicon-aluminum alloy matrix, the doping amount of titanium boride and silicon elements in the hardened layer is higher, forming a concentration gradient with the silicon-aluminum alloy matrix, and the hardened layer structure is finer, so that it has excellent characteristics such as high hardness, high density, and stable mechanical properties, which can effectively improve the wear resistance of the silicon-aluminum alloy and extend its service life; and the silicon-aluminum alloy maintains good strength and plasticity. In the process, the working gas is selected as an inert gas and a thermal reducing gas, which can improve the oxidation problem of the silicon-aluminum alloy to a certain extent.
[0041] Further, the specific process of hydrothermal is as follows:
[0042] The silicon-aluminum alloy obtained after plasma spraying is alkali-washed, then immersed in a mixed aqueous solution of nitric acid and trimesic acid, and reacted at 158-165° C. for 11-12 hours; cooled, washed, and dried to form a MOF layer;
[0043] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0 to 2.0 A / dm 2 , oxidation time is 30 to 90 minutes; take out, dry, and obtain a corrosion-resistant layer.
[0044] Furthermore, the mixed aqueous solution contains 27 to 35 g / L nitric acid and 20 to 25 g / L trimesic acid.
[0045] Furthermore, 0.1 M sodium hydroxide solution is used for alkaline washing for 30 to 60 seconds; after the alkaline washing, anhydrous ethanol and deionized water are used for washing in sequence, and then dried.
[0046] Furthermore, in the electrolyte, sulfuric acid is 170-190 g / L, citric acid is 20-30 g / L, and imidazole is 10-30 g / L.
[0047] In the above technical scheme, the surface (hardened layer) of the silicon-aluminum alloy is activated by alkali washing, and then placed in a mixed aqueous solution of nitric acid and trimesic acid. The activated silicon-aluminum alloy (hardened layer) can provide the required aluminum ions under the action of nitric acid, thereby forming Al-MOF in situ on the surface of the silicon-aluminum alloy (hardened layer) through a hydrothermal reaction. Affected by its nanoparticles and porous structure characteristics, it can effectively hinder the penetration and diffusion of corrosive media into the silicon-aluminum alloy, thereby improving the corrosion resistance of the silicon-aluminum alloy. Then the formed MOF layer is placed in an electrolyte containing imidazole, and the imidazole enters the Al-MOF pores and adsorbs, which can slow down the corrosion rate of the silicon-aluminum alloy and block the corrosive medium, thereby improving the corrosion resistance of the silicon-aluminum alloy. In addition, the surface of the silicon-aluminum alloy is oxidized in the electrolyte, and aluminum oxide is generated by anodization. The volume expansion blocks and closes the pores to form a corrosion-resistant layer; at the same time, the corrosion-resistant layer contains titanium diboride, which has excellent corrosion resistance and can also block the corrosive medium, further improving the anti-fouling and corrosion resistance of the silicon-aluminum alloy.
[0048] Further, the specific process of sealing is as follows:
[0049] The silicon-aluminum alloy obtained after hydrothermal treatment is placed in a silane hydrolysis solution, immersed for 5 to 10 minutes, taken out, blown dry, and placed at 100 to 120° C. for curing for 90 to 120 minutes to form a sealing layer;
[0050] The silane hydrolysis solution is prepared by the following process: mixing an alcohol aqueous solution and KH-560, adjusting the pH of the system to 3-4 with acetic acid, heating to 50-60° C., and standing for 5-24 hours to obtain;
[0051] The usage of KH-560 in the silane hydrolysis solution is 3-5wt%; the concentration of the alcohol aqueous solution is 60-90v%.
[0052] In the above technical scheme, the hydrolysis solution of KH-560 is placed on the surface of the silicon-aluminum alloy corrosion-resistant layer to condense it into a film, and the holes are sealed after curing and drying, thereby reducing the surface defects of the corrosion-resistant layer, preventing the penetration and diffusion of corrosive media in the environment, and improving the corrosion resistance of the silicon-aluminum alloy. In addition, the imidazole adsorbed in the corrosion-resistant layer can act as a cross-linking agent and catalyze the curing of the epoxy in KH-560 (γ-(2,3-epoxypropoxy)propyltrimethoxysilane), forming a steric hindrance for sealing, which helps to improve the strength and stability of the sealing layer; increase the cross-linking degree of the system, enhance the bonding strength of the layers, and improve the wear resistance, oxidation resistance, and corrosion resistance of the silicon-aluminum alloy.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] 1. The semi-solid forming process of silicon aluminum alloy described in the present invention uses inert gas as working gas, sprays alloy powder into aluminum liquid, and promotes nucleation and inhibits grain growth by stirring with airflow. At the same time, the temperature difference between alloy powder and aluminum liquid is used to make the melt supercooled, which provides driving force for nucleation, increases nucleation points in the melt, promotes non-spontaneous nucleation of initial silicon in the melt, and improves the nucleation rate of aluminum liquid, so that the prepared semi-solid slurry has good structure.
[0055] 2. The semi-solid forming process of a silicon aluminum alloy described in the present invention uses titanium boride in the alloy powder as a heterogeneous nucleation core to exert a solid solution strengthening effect, refine the structure, promote the transformation of the eutectic structure to a network configuration, and hinder the aggregation of the brittle eutectic phase, so that the strength and plasticity of the prepared silicon aluminum alloy are improved, and the corrosion resistance and friction and wear resistance are improved.
[0056] 3. The semi-solid forming process of a silicon-aluminum alloy described in the present invention heats the alloy powder to a molten state through plasma spraying technology, and sprays it on the surface of the silicon-aluminum alloy to form a high-silicon-aluminum coating highly doped with titanium boride, which can enable the silicon-aluminum alloy to maintain good strength and plasticity while improving its wear resistance and extending its service life.
[0057] 4. The semi-solid forming process of a silicon aluminum alloy described in the present invention forms Al-MOF in situ on the surface of the silicon aluminum alloy through a hydrothermal reaction. Affected by its nanoparticles and porous structure characteristics, it can effectively hinder the penetration and diffusion of corrosive media into the silicon aluminum alloy, thereby improving the corrosion resistance of the silicon aluminum alloy. Then, it is placed in an imidazole aqueous solution, and the imidazole enters the pores of the Al-MOF and is adsorbed, thereby improving the corrosion resistance of the silicon aluminum alloy; and the surface of the silicon aluminum alloy is oxidized to generate aluminum oxide, and the volume expansion blocks and closes the pores to form a corrosion-resistant layer; at the same time, the corrosion-resistant layer contains titanium diboride, which has excellent corrosion resistance and can also block corrosive media, further improving the anti-fouling and corrosion resistance of the silicon aluminum alloy. DETAILED DESCRIPTION
[0058] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] In the following specific implementations,
[0060] Aluminum powder: purity 99.9%, particle size 325 mesh; titanium powder: purity 99.9%, particle size 300 mesh; boron powder: purity 99.9%, particle size (D50) 10μm;
[0061] Aluminum-silicon alloy: AlSi50, from Hebei Xinlizhong Nonferrous Metals Group Co., Ltd.;
[0062] Aluminum silicon 20: AlSi20, particle size 100 mesh, sourced from Hebei Xinlizhong Nonferrous Metals Group Co., Ltd.;
[0063] The aluminum liquid includes the following components: by mass, Si: 8.0%, Mg: 0.5%, Cu: 0.2%, Ti: 0.08%, Mn: 0.05%, Fe: 0.05%, Zn: 0.03%, Zr: 0.05%, Y: 0.56%, and the balance is Al.
[0064] Embodiment 1: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0065] Step 1: Preparation of alloy powder:
[0066] Aluminum powder, titanium powder and boron powder are mixed, cold pressed, and held at 3T pressure for 90s; hot pressed sintering, the process conditions of hot pressed sintering are: sintering temperature 1600℃, pressure 30MPa, holding for 60min, protective atmosphere argon, to generate aluminum / titanium boride composite; mixed with aluminum silicon alloy, melted, spray deposited, the process conditions of spray deposition are: working gas is nitrogen, guide tube diameter is 3.5mm, melt temperature is 680℃, atomization deposition distance is 400mm, atomization gas pressure is 1.5MPa, to obtain alloy powder, the alloy powder includes the following components: by mass, Si: 25%, Ti: 8.2%, B: 3.8%, and the balance is Al;
[0067] Step 2: Semi-solid forming:
[0068] Mix the raw materials and heat them to 730℃ to melt them to form aluminum liquid. Cool the aluminum liquid to the slurry making temperature of 690℃, insert a powder spraying rod, and use argon or nitrogen as the working gas to spray alloy powder into the aluminum liquid to obtain a semi-solid slurry. The speed of the powder spraying rod is 800rpm, and the alloy powder accounts for 6% of the mass of the aluminum liquid.
[0069] Die casting, process conditions are: die casting temperature 320℃, injection speed 2m / s, injection pressure 40MPa, boost pressure 70MPa, holding time 10s; heat treatment, solution heat treatment: temperature 520℃, time 6h; cooling in 50℃ water for 5s; taking out, natural aging for 24h; aging treatment: temperature 180℃, time 6h, to obtain silicon aluminum alloy;
[0070] Step 3: Surface treatment:
[0071] (1) Plasma spraying technology is used to spray alloy powder onto the surface of silicon aluminum alloy. The process conditions are: argon flow rate 80L / min, hydrogen content 22%, spraying power 46kW, spraying distance 120mm, to form a hardened layer;
[0072] (2) The silicon-aluminum alloy obtained in the previous step was washed with 0.1 M sodium hydroxide solution for 30 seconds, and then washed with anhydrous ethanol and deionized water in sequence after alkaline washing, and dried; then immersed in a mixed aqueous solution (27 g / L nitric acid, 20 g / L trimesic acid), reacted at 158°C for 11 hours; cooled, washed, and dried to form a MOF layer;
[0073] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0A / dm 2 , oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L, imidazole 10g / L; take out, dry, and obtain the corrosion-resistant layer;
[0074] (3) Mix 60 wt% alcohol aqueous solution and KH-560, adjust the pH of the system to 3 with acetic acid, heat to 50 °C, and let stand for 5 hours to obtain a silane hydrolysis solution; the amount of KH-560 used in the silane hydrolysis solution is 3 wt%;
[0075] The silicon-aluminum alloy obtained in the previous step was placed in a silane hydrolysis solution, immersed for 5 minutes, taken out, blown dry, and placed at 100° C. for curing for 90 minutes to form a closed layer to obtain an alloy material.
[0076] Embodiment 2: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0077] Step 1: Preparation of alloy powder:
[0078] Aluminum powder, titanium powder and boron powder are mixed, cold pressed, and maintained at 4T pressure for 75s; hot pressed sintering, the process conditions of hot pressed sintering are: sintering temperature 1800℃, pressure 27MPa, heat preservation 60min, protective atmosphere argon, to generate aluminum / titanium boride composite; mixed with aluminum silicon alloy, melted, spray deposited, the process conditions of spray deposition are: working gas is nitrogen, guide tube diameter is 3.5mm, melt temperature is 710℃, atomization deposition distance is 450mm, atomization gas pressure is 1.0MPa, to obtain alloy powder, the alloy powder includes the following components: by mass, Si: 22%, Ti: 14.0%, B: 6.5%, and the balance is Al;
[0079] Step 2: Semi-solid forming:
[0080] Mix the raw materials and heat them to 750℃ to melt them to form aluminum liquid. Cool the aluminum liquid to slurry making temperature of 700℃, insert a powder spraying rod, and use argon or nitrogen as working gas to spray alloy powder into the aluminum liquid to obtain semi-solid slurry. The speed of the powder spraying rod is 900rpm, and the alloy powder accounts for 9% of the mass of the aluminum liquid.
[0081] Die casting, process conditions are: die casting temperature 320℃, injection speed 2m / s, injection pressure 40MPa, boost pressure 70MPa, holding time 10s; heat treatment, solution heat treatment: temperature 520℃, time 6h; cooling in 50℃ water for 5s; taking out, natural aging for 24h; aging treatment: temperature 180℃, time 6h, to obtain silicon aluminum alloy;
[0082] Step 3: Surface treatment:
[0083] (1) Plasma spraying technology is used to spray alloy powder onto the surface of silicon aluminum alloy. The process conditions are: argon flow rate 95L / min, hydrogen content 24%, spraying power 48kW, spraying distance 128mm, to form a hardened layer;
[0084] (2) The silicon-aluminum alloy obtained in the previous step was washed with 0.1M sodium hydroxide solution for 45 seconds, and then washed with anhydrous ethanol and deionized water in sequence after alkaline washing, and dried; then immersed in a mixed aqueous solution (30g / L nitric acid, 22g / L trimesic acid), reacted at 160°C for 11.5h; cooled, washed, and dried to form a MOF layer;
[0085] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.5A / dm 2 , oxidation time 60min; in the electrolyte, sulfuric acid 180g / L, citric acid 25g / L, imidazole 15g / L; take out, dry, and obtain the corrosion-resistant layer;
[0086] (3) Mix 75 wt% alcohol aqueous solution and KH-560, adjust the pH of the system to 3.5 with acetic acid, heat to 55 °C, and let stand for 12 hours to obtain a silane hydrolysis solution; the amount of KH-560 used in the silane hydrolysis solution is 4 wt%;
[0087] The silicon-aluminum alloy obtained in the previous step was placed in a silane hydrolysis solution, immersed for 8 minutes, taken out, blown dry, and placed at 110° C. for curing for 100 minutes to form a sealing layer to obtain an alloy material.
[0088] Embodiment 3: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0089] Step 1: Preparation of alloy powder:
[0090] Aluminum powder, titanium powder and boron powder are mixed, cold pressed, and maintained at a pressure of 5T for 60s; hot pressed sintering, the process conditions of hot pressed sintering are: sintering temperature 2000℃, pressure 25MPa, heat preservation 60min, protective atmosphere argon, to generate aluminum / titanium boride composite; mixed with aluminum silicon alloy, melted, spray deposited, the process conditions of spray deposition are: working gas is nitrogen, guide tube diameter is 3.5mm, melt temperature is 740℃, atomization deposition distance is 470mm, atomization gas pressure is 0.8MPa, to obtain alloy powder, the alloy powder includes the following components: by mass, Si: 20%, Ti: 19.9%, B: 9.1%, and the balance is Al;
[0091] Step 2: Semi-solid forming:
[0092] Mix the raw materials and heat them to 780℃ to melt them to form aluminum liquid. Cool the aluminum liquid to the slurry making temperature of 710℃, insert a powder spraying rod, and use argon or nitrogen as the working gas to spray alloy powder into the aluminum liquid to obtain a semi-solid slurry. The speed of the powder spraying rod is 1000rpm, and the alloy powder accounts for 12% of the mass of the aluminum liquid.
[0093] Die casting, process conditions are: die casting temperature 320℃, injection speed 2m / s, injection pressure 40MPa, boost pressure 70MPa, holding time 10s; heat treatment, solution heat treatment: temperature 520℃, time 6h; cooling in 50℃ water for 5s; taking out, natural aging for 24h; aging treatment: temperature 180℃, time 6h, to obtain silicon aluminum alloy;
[0094] Step 3: Surface treatment:
[0095] (1) Plasma spraying technology is used to spray alloy powder onto the surface of silicon aluminum alloy. The process conditions are: argon flow rate 90L / min, hydrogen content 26%, spraying power 50kW, spraying distance 135mm, to form a hardened layer;
[0096] (2) The silicon-aluminum alloy obtained in the previous step was washed with 0.1M sodium hydroxide solution for 60 seconds, and then washed with anhydrous ethanol and deionized water in sequence after alkaline washing, and dried; then immersed in a mixed aqueous solution (35g / L nitric acid, 25g / L trimesic acid), reacted at 165°C for 12h; cooled, washed, and dried to form a MOF layer;
[0097] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 2.0A / dm 2 , oxidation time 30min; in the electrolyte, sulfuric acid 190g / L, citric acid 30g / L, imidazole 20g / L; take out, dry, and obtain the corrosion-resistant layer;
[0098] (3) Mix 90 wt% alcohol aqueous solution and KH-560, adjust the pH of the system to 4 with acetic acid, heat to 60°C, and stand for 24 hours to obtain a silane hydrolysis solution; the amount of KH-560 used in the silane hydrolysis solution is 5 wt%;
[0099] The silicon-aluminum alloy obtained in the previous step was placed in a silane hydrolysis solution, immersed for 10 minutes, taken out, blown dry, and placed at 120° C. for curing for 120 minutes to form a closed layer to obtain an alloy material.
[0100] Comparative Example 1: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0101] Step 1 is the same as in Example 1, obtaining a silicon-aluminum alloy;
[0102] Step 2: Surface treatment:
[0103] (1) The silicon-aluminum alloy obtained in the previous step was washed with 0.1M sodium hydroxide solution for 30 seconds, washed with anhydrous ethanol and deionized water in sequence after alkaline washing, and dried; then immersed in a mixed aqueous solution (27g / L nitric acid, 20g / L trimesic acid) and reacted at 158°C for 11h; cooled, washed, and dried to form a MOF layer;
[0104] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0A / dm 2 , oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L, imidazole 10g / L; take out, dry, and obtain the corrosion-resistant layer;
[0105] (2) Mix 60 wt% alcohol aqueous solution and KH-560, adjust the pH of the system to 3 with acetic acid, heat to 50°C, and let stand for 5 hours to obtain a silane hydrolysis solution; the amount of KH-560 used in the silane hydrolysis solution is 3 wt%;
[0106] The silicon-aluminum alloy obtained in the previous step was placed in a silane hydrolysis solution, immersed for 5 minutes, taken out, blown dry, and placed at 100° C. for curing for 90 minutes to form a closed layer to obtain an alloy material.
[0107] Comparative Example 2: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0108] Step 1 is the same as in Example 1, obtaining a silicon-aluminum alloy;
[0109] Step 2: Surface treatment:
[0110] (1) Take the silicon-aluminum alloy obtained in the previous step and place it in an electrolyte for anodization at a current density of 1.0 A / dm 2, oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L; take out, dry, and obtain the corrosion-resistant layer;
[0111] (2) Mix 60 wt% alcohol aqueous solution and KH-560, adjust the pH of the system to 3 with acetic acid, heat to 50°C, and let stand for 5 hours to obtain a silane hydrolysis solution; the amount of KH-560 used in the silane hydrolysis solution is 3 wt%;
[0112] The silicon-aluminum alloy obtained in the previous step was placed in a silane hydrolysis solution, immersed for 5 minutes, taken out, blown dry, and placed at 100° C. for curing for 90 minutes to form a closed layer to obtain an alloy material.
[0113] Comparative Example 3: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0114] Step 1 is the same as in Example 1, obtaining a silicon-aluminum alloy;
[0115] Step 2: Surface treatment:
[0116] Plasma spraying technology was used to spray alloy powder (aluminum silicon 20) onto the surface of silicon aluminum alloy. The process conditions were: argon flow rate 80L / min, hydrogen content 22%, spraying power 46kW, spraying distance 120mm, to form a hardened layer.
[0117] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0A / dm 2 , oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L, a corrosion-resistant layer is formed to obtain an alloy material.
[0118] Comparative Example 4: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0119] Mix the raw materials and heat them to 730℃ to melt them to form aluminum liquid. Cool the aluminum liquid to the slurry making temperature of 690℃, insert a powder spraying rod, and use argon or nitrogen as the working gas to spray alloy powder (aluminum silicon 20) into the aluminum liquid to obtain a semi-solid slurry. The speed of the powder spraying rod is 800rpm, and the alloy powder accounts for 6% of the mass of the aluminum liquid.
[0120] Die casting, process conditions are: die casting temperature 320℃, injection speed 2m / s, injection pressure 40MPa, boost pressure 70MPa, holding time 10s; heat treatment, solution heat treatment: temperature 520℃, time 6h; cooling in 50℃ water for 5s; taking out, natural aging for 24h; aging treatment: temperature 180℃, time 6h, to obtain silicon aluminum alloy;
[0121] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0A / dm 2 , oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L, a corrosion-resistant layer is formed to obtain an alloy material.
[0122] Comparative Example 5: A semi-solid forming process of a silicon aluminum alloy, comprising the following processes:
[0123] The raw materials are mixed and heated to 730°C to melt to form aluminum liquid; the temperature is lowered to slurry making temperature of 690°C, and mechanically stirred at a speed of 200 r / min for 10 seconds to obtain a semi-solid slurry;
[0124] Die casting, process conditions are: die casting temperature 320℃, injection speed 2m / s, injection pressure 40MPa, boost pressure 70MPa, holding time 10s; heat treatment, solution heat treatment: temperature 520℃, time 6h; cooling in 50℃ water for 5s; taking out, natural aging for 24h; aging treatment: temperature 180℃, time 6h, to obtain silicon aluminum alloy;
[0125] Take the silicon-aluminum alloy obtained in the previous step and place it in the electrolyte for anodization at a current density of 1.0A / dm 2 , oxidation time 90min; in the electrolyte, sulfuric acid 170g / L, citric acid 20g / L, a corrosion-resistant layer is formed to obtain an alloy material.
[0126] Experiment: The silicon-aluminum alloys and alloy materials obtained in Examples 1-3 and Comparative Examples 1-5 were used to prepare samples, and their properties were tested and the test results were recorded:
[0127] Mechanical properties test: The tensile properties of the silicon aluminum alloy samples were tested using a tensile machine at a tensile rate of 1.5 mm / min;
[0128] Corrosion resistance test: using an electrochemical workstation, with a platinum electrode as the auxiliary electrode, and an exposed area of 1 cm 2 ,The experiment used 3.5% sodium chloride solution with a pH of 7 and a scanning speed of 1mV / s;
[0129] Wear resistance test: The oil lubrication friction and wear test was carried out at an oil temperature of 120°C using a friction and wear testing machine. The diameter of the grinding ball GCr15 was 10 mm, the frequency was 2 Hz, the reciprocating speed was 4 mm, and the test duration was 30 min.
[0130]
[0131] According to the data in the above table, we can clearly draw the following conclusions:
[0132] The silicon-aluminum alloys and alloy materials obtained in Examples 1-3 are compared with the silicon-aluminum alloys and alloy materials obtained in Comparative Examples 1-5. The test results show that:
[0133] Compared with the comparative example, the silicon aluminum alloy obtained in Examples 1-3 has higher tensile strength, yield strength and elongation, and the alloy material has lower friction coefficient and corrosion current density data. This fully demonstrates that the present invention achieves the improvement of the strength, plasticity and surface corrosion resistance and wear resistance of the silicon aluminum alloy.
[0134] Compared with Example 1, the surface treatment of the silicon aluminum alloy in Comparative Example 1 was not plasma sprayed; the surface treatment of the silicon aluminum alloy in Comparative Example 2 was anodized and sealed; the silicon aluminum alloy in Comparative Example 3 was plasma sprayed with aluminum silicon 20 and anodized. The friction coefficient and corrosion current density data of the alloy materials obtained in Comparative Examples 1-3 increased. It can be seen that the surface treatment process of the silicon aluminum alloy and the setting of the components used in the present invention can promote the improvement of its wear resistance and corrosion resistance.
[0135] Compared with Comparative Example 3, in the semi-solid forming process of Comparative Example 4, the alloy powder sprayed is aluminum silicon 20; the semi-solid forming process of Comparative Example 5 is mechanical stirring, and the tensile strength, yield strength, elongation, friction coefficient and corrosion current density data of the silicon aluminum alloy and alloy material obtained in Comparative Examples 4-5 are all deteriorated. It can be seen that the semi-solid forming process of the silicon aluminum alloy in the present invention is helpful to improve its mechanical properties and improve its wear resistance and corrosion resistance.
[0136] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0137] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A semi-solid forming process of silicon aluminum alloy, Features: Including the following processes: The raw materials are mixed and heated to melt to form aluminum liquid; alloy powder is added and semi-solid slurry is made to obtain semi-solid slurry; die casting is performed and heat treatment is performed to obtain silicon aluminum alloy; The silicon aluminum alloy is subjected to surface treatment, and the specific process is as follows: Plasma spraying technology is used to spray alloy powder onto the surface of silicon-aluminum alloy to form a hardened layer; Hydrothermal treatment to form a corrosion-resistant layer; sealing to form a closed layer; The alloy powder comprises the following components: by mass, Si: 20-25%, Ti: 8.2-19.9%, B: 3.8-9.1%, and the balance is Al; The alloy powder is obtained by mixing aluminum powder, titanium powder and boron powder, cold pressing, hot pressing and sintering to form an aluminum / titanium boride composite; and mixing with an aluminum silicon alloy, melting and spraying deposition; The specific process of the hydrothermal treatment is as follows: The silicon-aluminum alloy obtained after plasma spraying is alkali-washed, then immersed in a mixed aqueous solution of nitric acid and trimesic acid, and reacted at 158-165° C. for 11-12 hours; cooled, washed, and dried to form a MOF layer; The silicon-aluminum alloy obtained in the previous step is placed in an electrolyte containing imidazole for anodization at a current density of 1.0 to 2.0 A / dm 2 , oxidation time is 30 to 90 minutes; take out, dry, and obtain a corrosion-resistant layer.
2. A semi-solid forming process of a silicon aluminum alloy according to claim 1, Features: The aluminum liquid includes the following components: by mass, Si: 7.0-9.5%, Mg: 0.30-0.60%, Cu: 0.18-0.25%, Ti: 0.05-0.20%, Mn: 0.04-0.08%, Fe: ≤0.12%, Zn: ≤0.05%, Zr: 0.04-0.06%, RE: 0.20-0.60%, and the balance is Al.
3. The semi-solid forming process of a silicon aluminum alloy according to claim 1, Features: The process of semi-solid pulping is: The aluminum liquid is cooled to 690-710°C, a powder spraying rod is inserted, and alloy powder is sprayed into the aluminum liquid using inert gas as the working gas; the alloy powder accounts for 6-12% of the mass of the aluminum liquid, and the rotation speed of the powder spraying rod is 800-1000rpm.
4. The semi-solid forming process of a silicon aluminum alloy according to claim 1, Features: The process conditions of the hot pressing sintering are: sintering temperature of 1600-2000° C., pressure of 25-30 MPa, heat preservation for 60 minutes, and protective atmosphere of argon.
5. The semi-solid forming process of a silicon aluminum alloy according to claim 1, Features: The process conditions of the spray deposition are: the working gas is nitrogen, the diameter of the guide tube is 3.5 mm, the melt temperature is 680-740° C., the atomization deposition distance is 400-470 mm, and the atomization gas pressure is 0.8-1.5 MPa.
6. The semi-solid forming process of a silicon aluminum alloy according to claim 1, Features: The specific process of the sealing is as follows: The silicon-aluminum alloy obtained after hydrothermal treatment is placed in KH-560 hydrolysis solution, immersed for 5 to 10 minutes, taken out, blown dry, and placed at 100 to 120° C. for curing for 90 to 120 minutes to form a sealing layer.
Citation Information
Patent Citations
Preparation method for aluminum alloy or magnesium alloy semi-solid sizing agents
CN103170603A
Aluminum-based composite material and semi-solid preparation method thereof
CN114836658A
